Not in front of the children! The controversies of science and science communication for children and youth (Portuguese original version) - Luisa Massarani (JCOM: Journal of Science Communication, 2008)
Dialogue in science communication is a necessity - everybody agrees on it - because science and technology issues are involved in so many aspects of the citizens life, and in so many cases can raise suspects, fears, worries or, on the contrary, expectations and hopes. But who are the possible interlocutors for scientists and policy-makers? Everybody, says Luisa Massarani, beginning with children and teenagers. Also in such controversial and sensitive issues like AIDS or GMO.